Elbow arthroscopy in children and adolescents: analysis of outcome and complications - Jörg Nowotny; Sebastian Löbstein; Achim Biewener; Guido Fitze; Philip Kasten (European Journal of Medical Research, 2018)
Abstract Background Chondral or osteochondral lesions, post-traumatic contracture and loose bodies of the elbow are often associated with chronic pain, stiffness, repetitive swelling and joint blockages. Therefore, arthroscopy of the elbow is often used in the elderly for the treatment of osteochondral defects or arthrolysis. There are only a few reports and studies about arthroscopic therapy of the elbow in children and adolescents. This study assesses the clinical outcome of arthroscopic therapy in this age group. Methods In a retrospective study, children and adolescents who underwent an elbow arthroscopy in the period from 2010 to 2014 were included. The children were evaluated using the validated outcome measures Mayo Elbow Performance Score (MEPS), range of motion, pain on visual analog scale (VAS), Oxford Elbow Score (OES), quick dash and postoperative satisfaction. Furthermore, all complications were analyzed. Results In total, 27 patients were included. The mean (range) age was 14 (11–17) years, with a follow-up of 45 months. Fourteen (52%) were female and thirteen children (48%) were male. Twenty children had an arthroscopy due to osteochondritis dissecans and seven children for post-traumatic pain and stiffness. The mean (standard deviation) MEPS improved from 65 (15) to 96 (8; p = .005). The OES and quick dash were 93 and 5.4. The mean extension improved from − 15° (± 13.8) to 3° (± 10.2; p < .001). The mean flexion improved from 131° (± 13.4) to 137° (± 9.5; p = .003). Average pain on VAS was postoperative .2 (± .5), and 81.5% of all children had excellent or good results. There were no complications such as damage of nerves or blood vessels observed. Conclusion Elbow arthroscopy is an appropriate and safe treatment option in children and adolescents with good and excellent postoperative results.